The Nursing Professional Development Practice Model. Issue 3 (May 2022) - Rainford, Melanie; Uland, Cari; Youl, Zoe
Abstract : In the nursing professional development (NPD) specialty, the NPD practice model visually represents the NPD scope of practice and reflects a growing, vibrant specialty. It delineates the who, what, when, why, where, and how of the specialty practice and is approved by the American Nurses Association. This column reflects upon the evolution of the NPD practice model and delineates its updates in the fourth edition of the Nursing Professional Development: Scope and Standards of Practice .